Dismenore pada Mahasiswi Fakultas Kedokteran Universitas Bosowa - Maghfirah, Nurul; Putra, Bayu Pratama; Murnita, Ika Azdah (Fakultas Kedokteran Universitas Bosowa, 2023)
Dysmenorrhea is severe menstrual pain that causes a woman to visit a doctor or self-medicate by taking pain relievers. The impact that can be caused by dysmenorrhea is related to the quality of life, especially health and work productivity. This study aims to find out things related to the occurrence of dysmenorrhea in female students of the Faculty of Medicine, Bosowa University, in the academic year 2022-2023. The research method used is analytic observational with a case-control research design. This research was conducted on 134 female students, consisting of 67 case samples and 67 control samples. Data were analyzed using the chi-square test and 95% CI odds ratio test. The results of the bivariate analysis showed that there was a relationship between the age of menarche and the occurrence of dysmenorrhea, there was a relationship between body mass index and the occurrence of dysmenorrhea, there was a relationship between the duration of menstruation and the occurrence of dysmenorrhea, there is no relationship between stress levels and the occurrence of dysmenorrhea, and there is a relationship between family history with the occurrence of dysmenorrhea. This study concludes that there is a relationship between menarche age, body mass index, menstrual duration, and family history with the occurrence of dysmenorrhea.